2017
DOI: 10.1007/s13679-017-0283-6
|View full text |Cite
|
Sign up to set email alerts
|

Brown Adipose Tissue: an Update on Recent Findings

Abstract: Purpose of review New treatment approaches to weight loss and weight loss maintenance in humans are critical. Given its potential role in stimulating energy expenditure, brown adipose tissue (BAT) activation has become a trending topic as an anti-obesity treatment. Recent findings Most studies on BAT stimulation have been conducted in rodents and used cold stimulation. To date, few human trials exist that tested the effect of cold exposure on BAT. Those studies show that BAT contributes a small amount to ove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
111
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 163 publications
(127 citation statements)
references
References 105 publications
0
111
0
4
Order By: Relevance
“…The response of SNS during exercise is reported to increase from around 50-70% of the maximal oxygen uptake (VO 2max ) [43][44][45][46][47]. However, previous exercise studies did not focus on SNS, which makes previous research results regarding the correlation of exercise with BAT unclear [27,[48][49][50][51][52][53][54][55]. We hypothesized that vigorous-intensity physical activity (VPA) activates SNS, yielding an increase in BAT-d in the supraclavicular region.…”
Section: Introductionmentioning
confidence: 99%
“…The response of SNS during exercise is reported to increase from around 50-70% of the maximal oxygen uptake (VO 2max ) [43][44][45][46][47]. However, previous exercise studies did not focus on SNS, which makes previous research results regarding the correlation of exercise with BAT unclear [27,[48][49][50][51][52][53][54][55]. We hypothesized that vigorous-intensity physical activity (VPA) activates SNS, yielding an increase in BAT-d in the supraclavicular region.…”
Section: Introductionmentioning
confidence: 99%
“…Adipose-derived FGF21 also increases the expression of UCP1 and other thermogenic genes in adipose tissue by enhancing PGC-1α expression [17,18]. Browning of WAT and thermogenesis in BAT are major contributors to energy expenditure, which have been considered as effective strategies for the treatment of metabolic disorders [19]. It also has been proposed by several studies that WAT browning and BAT thermogenesis could be regulated through modulation of microbiota and their derived metabolites [20].…”
Section: Introductionmentioning
confidence: 99%
“…WAT stores excess energy in the form of triglycerides. In contrast, BAT increases energy expenditure by dissipating chemical energy as heat (thermogenesis), potentially counteracting obesity and related disorders [8]. Indeed, recent researches have shown that BAT transplantation could reduce the body weight gain and ameliorate glucose homeostasis in leptin deficient (ob/ob) obese mice and high-fat diet (HFD) -induced obese mice [9,10].…”
Section: Introductionmentioning
confidence: 99%